Proteome dataset of Hemileia vastatrix by LC–MS/MS label-free identification - Natália Faustino Cury; Daiane Gonzaga Ribeiro; Jonathan Dias de Lima; Pollyana da Nóbrega Mendes; Diana Fernandez; Wagner Fontes; Mariana S. Castro; Marcelo V. Sousa; Natália F. Martins; Angela Mehta (Data in Brief, 2022)
Here we describe the proteome of the fungus Hemileia vastatrix by label free mass spectrometry (LC–MS/MS). H. vastatrix is the causal agent of coffee rust disease, causing great economic losses in this crop. The objective of our work was to identify H. vastatrix proteins potentially involved in host colonization and infection, by exploring the shotgun proteomics approach. A total of 742 proteins were identified and are associated with several crucial molecular functions, biological processes, and cellular components. The proteins identified contribute to a better understanding of the metabolism of the fungus and may help identify target proteins for the development of specific drugs in order to control coffee rust disease. All data can be accessed at the Centre for Computational Mass Spectrometry – MassIVE MSV000087665 -https://massive.ucsd.edu/ProteoSAFe/dataset.jsp?task=cc71ad75f767451abe72dd1ce0019387